EEG of asymptomatic first‐degree relatives of patients with juvenile myoclonic, childhood absence and rolandic epilepsy: a systematic review and meta‐analysis. Issue 1 (27th March 2019) - Tashkandi, Mariam; Baarma, Duaa; Tricco, Andrea C.; Boelman, Cyrus; Alkhater, Reem; Minassian, Berge A.
ABSTRACT: Aims . Rolandic (RE), childhood absence (CAE) and juvenile myoclonic (JME) epilepsy encompass centrotemporal sharp waves, 3‐Hz spike waves and >3‐Hz spike or polyspike waves, respectively. Evidence abounds for genetic roles in all three syndromes, yet involved genes for the vast majority of patients remain unknown. It has long been proposed that while each disease is genetically complex, its specific EEG trait may represent a genetically simpler endophenotype. This meta‐analysis of the literature focuses on the frequency of EEG traits in clinically unaffected first‐degree relatives towards determining inheritance patterns of the EEG endophenotypes. Methods . We used the Preferred Reporting Items for Systematic Review and Meta‐Analysis for protocols (PRISMA‐P) and searched Medline, EMBASE, CINHAL and the Cochrane Central Register of Controlled Trials. Results . Following extensive screening, 15 studies were included with a total of 3, 858 asymptomatic relatives. The prevalence of 'abnormal' EEG waves was 21%, 42% and 33% for JME, CAE and RE, respectively, close to what would be expected based on Mendelian inheritance. However, breaking down the reported EEG abnormalities, most consisted not of the respective EEG signature traits ‐prevalences of which were as low as 5%‐ but of non‐specific EEG 'abnormalities'/variants. Conclusions . Prevalence of non‐specific EEG 'abnormalities'/variants in the general population ranges from 0.1 to 10%. Underlying this 100‐fold‐wide range is a spectrum of what is considered 'abnormal' or variant. The prevalences of 'abnormalities'/variants in asymptomatic siblings in RE, CAE and JME significantly exceed even the highest value in the general population and fall within Mendelian expectations. These results suggest that EEG 'abnormalities'/variants shared with the general population are enriched in the three syndromes and are endophenotypes inherited in a genetically simple near‐Mendelian fashion. Future work with modern EEG variant definitions should uncover genetic variants contributing to neuronal hypersynchrony in epilepsy.